2021
DOI: 10.12998/wjcc.v9.i14.3458
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic mastopathy in an elderly woman misdiagnosed as breast cancer: A case report and review of the literature

Abstract: BACKGROUND Diabetic mastopathy is a rare benign disease in clinical practice that mainly occurs in young and middle-aged women with type 1 diabetes. It has also been reported that this disease can be found in patients with type 2 diabetes and other autoimmune diseases, such as Hashimoto's thyroiditis, as well as in men. The pathogenesis of diabetic mastopathy is not yet clear, and it is easily confused with breast cancer due to their similar clinical manifestations and imaging features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…They may occur as single or as multiple lesions, may be unilateral or bilateral, and involve all quadrants of the breast. It has been shown that most cases of DM occur in the upper lateral/medial part of the breast (76%), and their size varies from 0.5 to 3.7 cm [ 3 ]. To date, in reported cases, axillary adenopathy was not present [ 14 , 15 ].…”
Section: Clinical Picture Diagnostic Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…They may occur as single or as multiple lesions, may be unilateral or bilateral, and involve all quadrants of the breast. It has been shown that most cases of DM occur in the upper lateral/medial part of the breast (76%), and their size varies from 0.5 to 3.7 cm [ 3 ]. To date, in reported cases, axillary adenopathy was not present [ 14 , 15 ].…”
Section: Clinical Picture Diagnostic Criteriamentioning
confidence: 99%
“…Tomaszewski et al [ 6 ] have suggested that the diagnosis of mastopathy should consist of the following criteria: (1) lymphocytic lobular and ductal inflammation with glandular atrophy; (2) lymphatic⁄ mononuclear perivascular inflammatory infiltrates, mainly of B cells; (3) dense, often keloid-like fibrosis; (4) presence of epithelial fibroblasts (EFB). Despite various clinical criteria proposed to date, the diagnosis of DM is not unequivocal and often requires further diagnostic workup due to its high similarity to breast cancer in clinical presentation and at imaging studies [ 3 ].…”
Section: Clinical Picture Diagnostic Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic mastopathy, also known as fibrous mastopathy, is a rare condition that comprises less than 1% of benign breast pathologies and is a known complication of type 1 diabetes mellitus (T1DM) [1]. This disease affects 0.6% to 13% of young and middle-aged premenopausal females with T1DM, but there have been infrequent reports of diabetic mastopathy occurring in patients with type 2 diabetes mellitus, the elderly, and males [1][2][3][4]. Diabetic mastopathy was first described by Sloer and Khardori in 1984 and was officially named by Logan and Hoffman in 1989 [5,6].…”
Section: Introductionmentioning
confidence: 99%